The Better Obstetrics in Rural Nigeria (BORN) Study An Impact Evaluation of the Nigerian Midwives Service Scheme - Okeke, Edward N. (RAND Corporation, 2015)
The Midwives Service Scheme (MSS) was introduced in 2009 to increase access to skilled care for women in rural underserved areas of Nigeria. To evaluate the impact of the MSS, researchers conducted household and clinic surveys, focus group discussions and in-depth interviews, and compared changes in pregnancy and birth outcomes in MSS areas to changes in comparison areas. They found smaller than anticipated effects.